The Evaluation Simulator: A New Approach to Training Music Performance Assessment - Waddell, George; Perkins, Rosie; Williamon, Aaron (Frontiers in Psychology, 2019)
A growing body of work has examined the act of evaluating the quality of a musical performance. This article considers the domain of training evaluative skills in musicians, presenting assessment as a form of performance to be taught and demonstrating a gap in opportunities for trainees to develop evaluative skills within the heightened environments of live assessment scenarios. To address these needs, the concepts of Immersive Virtual Environments (IVEs) and distributed simulation are described, highlighting their use in training and research in other performance domains. Taking this model as a starting point, we present the Evaluation Simulator as a new tool to study and train performance evaluation. Potential applications of this prototype technology in pedagogical and research settings are then discussed.